IMPLIKASI TEORI SOSIAL KRITIS TERHADAP PERKEMBANGAN RISET PSIKOLOGI - Fathur Rahman (Paradigma, 2009)
Although the terminology of critical psychology is relatively recent, there have always been psychologists who opposed the field’s emerging identity and practices. Today, critical psychologists present a multitude of philosophical, scientific, and political objection. In response, critical works to identify mainstream of psychology’s unacknowledged assumption, they demonstrate their impact on psychology and in the larger society, and propose alternative theoretical frameworks research methods, and professional practices. More critics to the mainstream of psychologist as shown below ; 1) by focusing on the individual rather than the group and larger society, mainstream psychology overemphasizes individualistic values, hinders the attainment of mutuality and community, and strengthens unjust institution; 2) mainstream psychology’s underlying assumption and institutional allegiances disproportionately hurt members of powerless and marginalized groups by facilitating inequality and oppression; and 3) these unacceptable outcomes occur regardless of psychologists’ individual or collective intentions to the contrary.Keywords: critical social theory, critical psychology, psychological research